Hydatid lung cysts with hemoptysis mimicking pulmonary tuberculosis (Indian Journal of Case Reports, 2020)
Hydatid cyst of the lung is one of the rare causes of hemoptysis and often diagnosed late. Cystic echinococcosis is the larval cystic stage (echinococcal cysts) of a small taenia-type tapeworm (Echinococcus granulosus) that may cause illness in intermediate hosts, generally herbivorous animals and people who are infected accidentally. We present the case of multiple hydatid cysts in a 10-year-old boy presenting with hemoptysis from an endemic area but with no history of contact. Radiological investigations done were inconclusive, and the patient was started on anti-Koch’s Therapy (AKT) based on a high clinical suspicion. Surgical intervention was planned after 4 months of therapy due to the non-resolution of symptoms and progression of the disease. Histopathology was suggestive of multiple hydatid cysts occupying the right lung lower lobe. The patient was started on Tab Albendazole and the follow-up period was uneventful. A possibility of hydatid cyst in cases of lung infections should be kept in endemic areas irrespective of the history and radiological features. Complete evaluation, along with tissue diagnosis, is important for establishing a confirmative diagnosis of tuberculosis. Empirical treatment with AKT, in cases of suspicion, should be avoided.